Competence of Althaeaofficinalis Seed Extract in control of Haemorrhoids in comparison with Daflon - Maaz Ahmad, Fizza Anwar, Wasif Majeed Chaudhary, M. Faheem Anwer, Mussab Ahmad, Syma Arshad, Asma Kanwal, H. Ahmad, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The use of medicinal plants in herbalism has been documented for thousands of years, with evidence dating back to ancient civilizations such as the, Chinese, Greeks and Egyptians1. Extensive clinical studies have demonstrated that Althaeaofficinalis has properties that promote healing of ulcers2. Aim: To evaluate effectiveness of Althaeaofficinalis seed extract compared to Daflon (diosmin plus hesperidin) in treating hemorrhoids. Methods: A double-blind, randomized clinical trial was carried out in Lahore's urban community. Patients with acute hemorrhoids were randomly divided into two parallel groups, each with 60 participants, for a one-week period. The selection of family physicians for the study was done randomly.6,7,8 Interventions: In the beginning, the participants were given either two capsules of 500mg Althaea seed extract or two tablets of Daflonin morning and evening for four days, followed by two capsules/tablets daily for the next three days. The primary measure of effectiveness was the alleviation of symptoms and signs.9,10 Results: Both groups demonstrated similar improvement from first day tolast day. The intensity of symptoms such as itching, tenesmus, and bleeding ,swelling, painetc reduced markedly in both groups, but the reduction was fast in the Althaeaofficinalis seed extract group observed initial days of the trial. Practical Implications: Estimated prevalence of haemorrhoids ranges from 2.9% to 27.9% worldwide.11,12.13 However, due to cultural practices, it is often ignored and left untreated, It is therefore essential to design preventive measures and control strategies for hemorrhoids. Conclusion: Both Althaea and Daflon were found relieving haemorrhoidal signs and symptoms of hemorrhoids. However, the use of Althaea seed extract resulted in quicker relief and it may be used as good alternative to Daflon. Keywords: Haemorrhoids ,Altthaea seed extract, Althaeaofficinalis, double blind, tenesmus, bleeding,